Humans can extract distance and velocity from vestibular perceived acceleration - von der Heyde, M.; Riecke, B. E.; Cunningham, D. W.; Bülthoff, H. H. (Cognitive Neuroscience Meeting; Journal of Cognitive Neuroscience, 63C 77, 2000)
Abstract: Purpose: The vestibular system is known to measure accelerations for linear forward movements. Can humans integrate these vestibular signals to derive reliably distance and velocity estimates? Methods: Blindfolded naive volunteers participated in a psychophysical experiment using a Stewart-Platform motion simulator. The vestibular stimuli consisted of Gaussian-shaped translatory velocity profiles with a duration of less than 4 seconds. The full two-factorial design covered 6 peak accelerations above threshold and 5 distances up to 25cm with 4 repetitions. In three separate blocks, the subjects were asked to verbally judge on a scale from 1 to 100 traveled distance, maximum velocity and maximum acceleration. Results: Subjects perceived distance, velocity and acceleration quite consistently, but with systematic errors. The distance estimates showed a linear scaling towards the mean and were independent of accelerations. The correlation of perceived and real velocity was linear and showed no systematic influence of distances or accelerations. High accelerations were drastically underestimated and accelerations close to threshold were overestimated, showing a logarithmic dependency. Conclusions: Despite the fact that the vestibular system measures acceleration only, one can derive peak velocity and traveled distance from it. Interestingly, even though maximum acceleration was perceived non linear, velocity and distance was judged consistently linear.
Keywords: Riecke; Riecke_2000; bernhard-riecke; iSpaceWeb; markus-von-der-heyde; posterWithoutPaper; talkWithoutPaper